Adoption rates of laparoscopic techniques for colorectal resections among Brazilian surgeons: limiting factors affecting incorporation into daily practice - Campos,Fábio Guilherme (2019)
ABSTRACT Routine adoption of laparoscopy in clinical practice and Medical Residency has not been widely evaluated in Brazil so far. Aim: To take an overview on the adoption and limitations concerning the use of laparoscopic techniques among Brazilian colorectal surgeons. Methods: A questionnaire was sent to 1870 SBCP filiated members, containing personal and professional data such as sex, age, length and local of practice, SBCP filliation, number of procedures, treatment of cancer and laparoscopy limitations. Results: 418 members (22.4%) sent their response (80% men and 20% women). 110 members (26.3%) affirmed they don't perform any laparoscopic procedure, while 308 (73.7%) have already adopted laparoscopy as a routine. An average number of 7.6 laparoscopic colorectal procedures were declared to be performed per month (1 to 40 procedures). Laparoscopic adoption rates were favourably influenced by young age members (46% vs. 28%) and affiliation to University hospitals (p = 0.01). Conversely, surgeons from private clinic showed a greater tendency of no adoption. Among the 308 responders, 106 (34.4%) have already surpassed more than 100 laparoscopic cases, and 167 (54.2%) reported an experience of more than 50 operated patients. The group of surgeons not using minimally invasive techniques incriminated lack of training (73.6%) and laparoscopic instruments availability (27.3%) as the main reasons for no adoption. Conclusions: Adoption rate of laparoscopic techniques to treat colorectal diseases is still low (at least 17%). Future efforts should focus on providing supervised training, proctorship during the initial experience and help instrumental acquisition in centers willing to change their routine and perspectives.